The Africa Problem of Global Urban Theory: Re-conceptualising Planetary Urbanisation - Garth Myers (Revue Internationale de Politique de Développement)
This paper works to address what I consider the enduring ‘Africa problem’ in global urban theory. I engage and critique selected relevant urban thought from the Globalization and World Cities research group, from Henri Lefebvre and from the new wave of urban theorisation inspired by Lefebvre’s (1970) idea of ‘complete, planetary urbanisation.’ I argue that urbanisation in Africa, largely absent from Lefebvre’s works, presents new twists that are better understood from outside a Eurocentric framework. I propose the possibilities of urban comparativism built from theories and conceptualisations that emerge from the global South and that can be utilised to compare non-Western cities’ urbanisation processes. I use case studies from Dakar and Zanzibar to examine the production of what Chinese urbanists detail as a ‘village’ in the city, on the edge of the city, and in the suburbs over the last half-century and the complexities and comparability of urbanisation processes in these settings. I end with reflections on the implications of these cases for any claims for universalising the twenty-first century’s processes of urbanisation and urbanism across the planet. My main finding for urban policy and planning practice is the documentation of the relevance and value of South–South comparisons of urbanisation processes for development.